Mucinous Cystadenoma Arising in a Uterine Isthmocele: A Case Report - Carvalho, Jesus Paula; Silva, Alexandre Silva e; Kleine, Rodolpho Truffa; Bertolazzi, Marília Albanezi; Fernandes, Rodrigo Pinto; Carvalho, Filomena Marino (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Isthmocele is a discontinuation of the myometrium at the uterine scar site in a patient with a previous cesarian section (CS). The cause of isthmocele appears to be multifactorial. Poor surgical technique, low incision location, uterine retroflection, obesity, smoking, inadequate healing of scars, and maternal age are possible related factors. Most patients with this condition are asymptomatic. However, women can present with postmenstrual bleeding, pelvic pain, subfertility, dysmenorrhea, infertility, and scar abscess. Brazil has one of the world's highest cesarean section rates. One of the consequences of the rising rate of CS is the isthmocele, an emerging female health problem. Here we report a case of mucinous cystadenoma arising in a uterine isthmocele, a complication, as far as we could investigate, not yet described in the literature.
Keywords: isthmocele; niche; diverticulum; deficient uterine scar; scar pouch; mucinous cystadenoma